Quantification of ADHD medication in biological fluids of pregnant and breastfeeding women with liquid chromatography: a comprehensive review - De Hondt, Lena; Cosemans, Charlotte; Plusquin, Michelle; Mangelings, Debby; Van Eeckhaut, Ann; Tommelein, Eline (Frontiers in Public Health, 2024)
Attention Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that has long been considered a concern only in the paediatric population. However, symptoms often sustain into adulthood and may require medication. For women with ADHD, this also means dealing with the disorder during the reproductive period. Medication safety during pregnancy and breastfeeding is a critical concern, and the potential transfer of ADHD medication to infants remains a topic of scientific interest. The quantification of ADHD medications in both maternal blood and breast milk are vital for understanding their pharmacokinetics and potential exposure risks for (nursing) infants. This review aims (1) to compile and critically assess existing research on the transfer of ADHD medications into breast milk and the potential implications for nursing infants and (2) to provide a comprehensive overview and discussion of the literature regarding the quantification of methylphenidate, amphetamine, atomoxetine, viloxazine, guanfacine, clonidine and bupropion in the blood, urine, oral fluid, and breast milk with liquid chromatography. A literature search was conducted using PubMed, Scopus, and Web of Science, to identify relevant articles published from January 2014 up to December 2023. We illustrate the lack of methods to simultaneously monitor multiple ADHD medications as well as the lack of developed methods for breast milk. Finally, we highlight the need for continued research to refine our understanding of medication transfer into breast milk and potential risks, and to develop clinical guidelines to support mothers with ADHD in making informed choices regarding medication use during pregnancy and lactation.